محــددات اختيــار التخصــص عنـد طلـبـة الجامعـة - منصوري، سعد الدين, قعيد، عبد البديع (جامعة الوادي university of Eloued, 2021)
الملخص: هدفت الدراسة إلى الكشف عن محددات اختيار التخصص عند التوجيه لدى الطالب الجامعي وهل تختلف هذه المحددات حسب الجنس والعمل والفرع. حيث استخدمنا المنهج الوصفي الاستكشافي على مرحلتين باستعمال المقابلة على عينة عرضية مقدرة بـــ 30 طالبا ثم استخرجنا المحددات واعددنا بها استبيانا وزعناه بعد التحكيم على عينة عرضية مكونة من 313 طالبا من كلية العلوم الاجتماعية والانسانية وكلية العلوم الاقتصادية والتجارية وعلوم التسيير من أجل حساب تكرارات والنسب المئوية، حيث توصلنا إلى أن محدّدات اختيار التخصص هي كثيرة ولكن من أهم هذه المحددات نجد أولا أنه يستفيد من التخصص الذي اختاره في حياته الشخصية، أما ثانيا رغبته في التخصص. كما أنه لا يوجد اختلاف بين الذكور والإناث والموظفين وغير الموظفين في ترتيب محددات اختيار التخصص لدى الطلبة. كما أنه يوجد أيضا اختلاف بين طلبة فرع العلوم الإنسانية والاجتماعية وطلبة فرع العلوم الاقتصادية والتجارية وعلوم التسيير في ترتيب محددات اختيار التخصص. The study aimed to reveal the determinants the major's choice for directing the university student and whether these determinants differ according to gender, work and branch. Where we used the descriptive exploratory approach in two stages using an interview sample of 30 students, then extracted the determinants and prepared a questionnaire with it, which we distributed after committment sample of 313 students from the social and Human sciences department and the Economic Business Sciences and Management Sciences department in order to calculate the frequencies and percentages, As we concluded that the determinants of major's choice are many, but one of the most important is that first of all : we find that he benefits from the specialization that he has chosen in his personal life, and secondly, his desire to specialize. In addition, there is no difference between males and females, employees and non-employees, in the order of determinants for choosing the major among students. There is also a difference between students of the humanities and social sciences branch and students of the economic, business and management sciences branch in order of determinants for choosing the major.
دراسة استكشافية لدى طلبة سنة ثانية ليسانس - جامعة الوادي
مذكرة ماستر علم الاجتماع تخصص إرشاد وتوجيه
Keywords: التوجيه التربوي، التوجيه الجامعي; Orientation scolaire, orientation universitaire; educational guidance, university guidance